Rancang Bangun Sistem Keamanan Brankas Pintar Menggunakan Teknologi Internet of Things (IoT) dan Kecerdasan Buatan (AI): Telekomunikasi Militer - Abethnego; Vincensius Arga Yoda; Muhammad Ridwan (Pustaka Poltekad, 2026)
The development of Internet of Things (IoT) and Artificial Intelligence (AI) technology has opened up new opportunities in the development of modern security systems, including for valuable storage devices such as smart safes. This research aims to design and build a smart safe security system that utilizes the integration of IoT sensors and AI-based analytics to improve protection effectiveness. The methods used include designing microcontroller-based hardware, using motion, vibration, and camera sensors, and implementing AI algorithms to detect suspicious activity in real-time and perform predictive analytics on access patterns. The results obtained show that the system is capable of providing remote monitoring, early warnings through notifications to the user's device, and more accurate threat detection. However, the integration of IoT and AI also presents challenges in terms of data security and privacy, requiring the implementation of encryption and regular audits. With this design, the smart safe is expected to be an innovative solution that is not only reactive, but also proactive in maintaining the security of money and valuables.